Dissolution magnitude and kinetics of ZnO nanoparticles mediated by water are dependent on O vacancy abundance: the environmental implications - He, Hongping (2022)
Metal oxide nanoparticles (NPs) dissolution in water environment is an important issue with regard to their environmental behaviors. The metal ion dissolves from surface defective site, but the effect of defect abundance remains largely unknown. This study aims to reveal this effect using ZnO NPs and O vacancy as the model system. The abundance of O vacancy is modulated by using different precursors and changing calcination atmosphere and temperature. X-ray photoelectron spectroscopy characterization shows that surface O vacancy abundance is effectively modulated to be distributed in a wide range from 15.3% to 41.8%. The deviation of O/Zn mole-ratio from 1.00 is used to denote O vacancy abundance in the bulk crystal, and the deviation reaches up to 0.32. Experiments show that the kinetics and magnitude of ZnO NPs dissolution vary in H2O, which are highly dependent on O vacancy abundance. In comparison, the specific surface area and aggregation state take minor roles. Particularly, Zn2+ dissolution rate in the first hour is more linearly correlated with surface O vacancy abundance than with specific surface area. Defects and their abundances should thus be co-considered with other physicochemical properties to fully understand the dissolution behaviors of metal oxide NPs in water environment. This study is of significance in comprehensively assessing and predicting the environmental risk of metal oxide NPs.